Knowledge Management and Emotional Intelligence Toward Workforce Productivity: The Mediating Role of Employee Innovation - Yuyus Yudistria; Rhian Indradewa; Jul Aidil Fadli; Jazi Munjazi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In an increasingly competitive organizational environment, firms must leverage knowledge resources and employees’ emotional capabilities to stimulate innovative actions that enhance productivity. This study examines the effects of knowledge management and emotional intelligence on workforce productivity through innovative work behavior in the clothing industry in West Java. A quantitative survey approach was applied by distributing questionnaires to employees over a three-month period from November 2023 to January 2024. Data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The findings demonstrate that knowledge management and emotional intelligence significantly promote innovative work behavior. Furthermore, innovative work behavior has a significant positive effect on workforce productivity and acts as a mediating mechanism linking the antecedent variables to productivity outcomes. These results indicate that productivity improvement is more effectively achieved when organizations convert knowledge assets and emotional competencies into innovative work practices. The study emphasizes the strategic role of innovative work behavior in translating organizational resources into measurable productivity gains within the clothing industry context.